Barriers and opportunities for climate adaptation: The water crisis in Greater S\~ao Paulo - Ana Helena A. P. Cavalcante (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2015)
This paper analyzes the current water crisis in Greater S\~ao Paulo. It is based on a diagnosis of the main barriers that impeded government and other stakeholders at different governance scales to take action to guarantee a secure water provision. The objective was to discuss why there was a lack of preparation of this region to the occurring of a prolonged drought and which adaptation measures could have been taken to avoid or diminish its effects on water supply. The analysis is the result of an in-depth explanatory case study and field research, which had as its primary evidence a set of twelve semi-structured interviews made in the studied region in March and April 20151. Further evidence was extracted from newspaper articles, government reports and scientific publications. The key reference of this lecture is the literature on barriers to adaptation to climate change. Ostrom's (2009) Social-Ecological Systems (SES) framework provided the analytical framework used to analyze the collected data and to understand the interactions among core subsystems that affect each other and are linked to social, economic, and political settings and related ecosystems. The results comprehend ten barriers that were encountered in the interactions that contributed to the water crisis. We conclude that the misrepresentation of the interests of the population in having a secure water provision and the risky behavior of water managers influenced the crisis. Further we argue that the lack of governance mechanisms and the political power concentration, which characterizes the actual governance system, are central in the explanation of the ongoing crisis.
Keywords: 330; resource access/control; water security; climate adaptation; Brazil; urban development